Diversidade florística e classificação e caracterização das unidades de paisagem em área de lajedo no cariri paraibano – o caso do Lajedo da Salambaia - Medeiros, Joseilsom Ramos de (2019)
The Caatinga has been one of the vegetation formations most affected by human activities and has historically suffered from degradation that threatens the existence of what remains. Even though in Paraíba there are landscapes where the Caatinga has been greatly altered over the years, in this state it is still possible to find remnants of Caatinga, important environments that demonstrate the relevant diversity that still exists, where it is possible to find endemic species of this biome. In the Caatinga, in its largest portion, species with xeric characteristics predominate, but in areas that are under the influence of rocky outcrops, mainly in Cariri Paraibano, it is possible to find species from more humid environments. The studied area comprises the entire extension of the private property called Fazenda Salambaia, located in Cariri Paraibano. For the development of this work, fieldwork was carried out in order to carry out floristic and landscape surveys. With regard to methodologies, part of the proposal developed by Cámara and Díaz del Olmo (2004), called Linear Transect Method for Phanerophytes and Caméphytes – MTLFC was applied. As for the observation and characterization of the landscape units, a field notebook adapted from the work “Cartografia de Paisagens”, by Cavalcanti (2014) was taken as a basis. As for the choice of methodologies, the first has a phytosociological character, aimed at identifying phytophysiognomies expressed in the landscape, while the second has a more descriptive character of system interactions. Therefore, the two complement each other for a better understanding of the landscape of the studied area. In all, seventy linear transects were carried out, which correspond to seven plots, distributed in areas that show few signs of human use, as well as transects were carried out in areas with significant human interference. From the floristic surveys, it was possible to identify 3,128 individuals, belonging to 34 families, 89 genera and 103 botanical species, distributed among the subshrub, shrub, and arboreal habits. Most of the sampled species are Caatinga species. Although the number of species typical of humid and sub-humid areas is low, it draws attention, as the presence of some is not common in the semi-arid region. As for the characterization of landscape units, a map covering ten units was generated, as well as a standard section. The results presented showed how relevant is the existing floristic and landscape diversity at Fazenda Salambaia. Through the floristic surveys it was possible to carry out a diagnosis of the existing diversity in the studied area, expanding the knowledge about the Caatinga and the different vegetation patterns. The floristic surveys supported the spatialization of landscape units, elaborated through an integrated view of the elements and processes of the environment, showing that the mapping of units is an important product for environmental planning and territory management.